(untitled) (CIPEEX, 2022)
ONE OF THE MOST UNFORTUNATE SITUATIONS IN BRAZILIAN HEALTH IS FOUND IN QUEUES AT HEALTHCENTRES, WHERE PEOPLE OFTEN SPEND A CONSIDERABLE TIME OF THEIR DAYS IN QUEUES WAITING TO BEATTENDED TO. IN ORDER TO SOFTEN THIS PROBLEM AND GUARANTEE MORE FREE TIME FOR PEOPLE WHOEXPECT TO BE SEEN AT CLINICS AND HEALTH POSTS, WE STARTED THE PRODUCTION OF THE PASS+. INMAKING THE IDEA FOR THIS APPLICATION, WE USED THE BEST SOFTWARE ENGINEERING PRACTICES FORPROJECT MANAGEMENT AND REQUIREMENTS CREATION, RESPECTIVELY SUPPORTED BY SCRUMBAN (ACOMBINATION OF THE ORGANIZATIONAL FRAMEWORKS "SCRUM" AND "KANBAN") AND LEAN INCEPTION,DEFINING THAT THE APPLICATION WILL HAVE SUPPORT FOR IOS AND ANDROID, LATER HAVING A WEBVERSION. IN ADDITION TO DEFINING THAT THE APPLICATION WILL BE A SIMPLE WAY OF NOTIFYING THECUSTOMER ABOUT AN APPOINTMENT AND WILL FACILITATE THE APPOINTMENT SCHEDULING PROCESS, LEANINCEPTION ALSO FACILITATED THE PROCESS OF DEFINITION OF NON-FUNCTIONAL REQUIREMENTS, SUCH ASISSUES RELATED TO ACCESSIBILITY, WHICH WILL BE A KEY POINT IN THE CREATION OF THIS PROJECT, AS IT ISAN APPLICATION THAT WILL BE AVAILABLE FOR ALL AGES. IN ADDITION, WE CAN ALSO MENTION FIGMA,WHICH IS A GREAT ALLY IN THE DESIGN AND PROTOTYPING PROCESS, HELPING TO VALIDATE WHAT MUST BEIN THE APP AND HOW IT WILL BE IMPLEMENTED. FINALLY, IT CAN BE SAID THAT IN THE CURRENT PHASE OFTHE PROJECT, WE ARE IN THE PROTOTYPE VALIDATION PERIOD IN FIGMA, WHICH IS ALREADY DYNAMIC ANDUSABLE, WITH THE PROSPECT THAT IN THE NEXT SPRINT (IMPLEMENTATION CYCLE OF ONE OR MOREFUNCTIONALITIES WITHIN THE SCRUM MODEL) WE WILL START CODING THE PROJECT. KEYWORDS: QUEUES,REDUCTION, HEALTH, ACCESSIBILITY